The repair of historic timber structures - Yeomans, David T. (Thomas Telford, 2003)
England has a surprising number of timber-framed buildings which mostly date from before 1700 and are normally listed buildings. There is now an increasing demand for these buildings to be adapted to suit modern day requirements. This book takes a practical approach and discusses two types of structure.